Dysregulation of the Nitric Oxide/Dimethylarginine Pathway in Hypoxic Pulmonary Vasoconstriction—Molecular Mechanisms and Clinical Significance - Hannemann, Juliane; Böger, Rainer (Frontiers in Medicine, 2022)
The pulmonary circulation responds to hypoxia with vasoconstriction, a mechanism that helps to adapt to short-lived hypoxic episodes. When sustained, hypoxic pulmonary vasoconstriction (HPV) may become deleterious, causing right ventricular hypertrophy and failure, and contributing to morbidity and mortality in the late stages of several chronic pulmonary diseases. Nitric oxide (NO) is an important endothelial vasodilator. Its release is regulated, amongst other mechanisms, by the presence of endogenous inhibitors like asymmetric dimethylarginine (ADMA). Evidence has accumulated in recent years that elevated ADMA may be implicated in the pathogenesis of HPV and in its clinical sequelae, like pulmonary arterial hypertension (PAH). PAH is one phenotypic trait in experimental models with disrupted ADMA metabolism. In high altitude, elevation of ADMA occurs during long-term exposure to chronic or chronic intermittent hypobaric hypoxia; ADMA is significantly associated with high altitude pulmonary hypertension. High ADMA concentration was also reported in patients with chronic obstructive lung disease, obstructive sleep apnoea syndrome, and overlap syndrome, suggesting a pathophysiological role for ADMA-mediated impairment of endothelium-dependent, NO-mediated pulmonary vasodilation in these clinically relevant conditions. Improved understanding of the molecular (dys-)regulation of pathways controlling ADMA concentration may help to dissect the pathophysiology and find novel therapeutic options for these diseases.